Zakat Produktif sebagai Mekanisme Ekonomi Mikro Islam dalam Menguatkan Ketahanan Ekonomi Rumah Tangga Dhuafa - Muhammad Rizqallah; Mursal (Ameena Journal, 2025)
Household economic resilience among dhuafa remains a crucial issue in achieving inclusive and equitable economic development, particularly within Muslim societies. Islamic economic instruments such as zakat possess significant potential to strengthen the economic capacity of vulnerable groups when managed productively. Although productive zakat has been widely implemented as a form of economic empowerment, studies that position it as an integrated mechanism within Islamic microeconomics remain limited. Therefore, this article aims to examine the role of productive zakat as an Islamic microeconomic mechanism in strengthening the economic resilience of dhuafa households. This study employs a library research method by reviewing and analyzing relevant literature, including books, academic journal articles, and scholarly documents related to productive zakat, Islamic microeconomics, and household economic resilience. The collected data are analyzed using a descriptive-analytical approach to identify key patterns, existing findings, and research gaps within previous studies. The findings indicate that productive zakat has strategic potential in enhancing income stability, business sustainability, and economic adaptability of dhuafa households. However, most existing studies tend to conceptualize productive zakat primarily as a social welfare program rather than as an integral component of Islamic microeconomic systems. This article concludes that productive zakat can more effectively strengthen household economic resilience when managed through integrated mechanisms that include business assistance and capacity building. The main contribution of this study lies in reinforcing the conceptual understanding of productive zakat as a sustainable Islamic microeconomic mechanism oriented toward strengthening the long-term economic resilience of dhuafa households.